Socialization on the Role of Islamic Banking in Encouraging the Progress and Development of MSMEs - Noval; Abdul Jalil; Ahmad Haekal; Fatma; Khusnul Khatimah; Muh. Imam Fur’qan; Moh. Mukhasyaf (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing significantly to economic growth, employment, and poverty alleviation. However, limited access to financing sources that suit their needs is a significant obstacle for MSMEs in developing their businesses. This research explores the role of Islamic banking as an alternative solution in supporting the development of MSMEs. Through community service activities at SMA 1 Sidue, we delivered material on Islamic banking and developing MSMEs to 100 student participants. An interactive lecture method was used to improve understanding, followed by a discussion session to encourage active participation of the participants. The evaluation results showed an increase in students' understanding of Islamic banking, including financing products that comply with Sharia principles and the challenges and opportunities faced by MSMEs. This activity is expected to educate MSME players on the benefits of Islamic banking and strengthen their capacity to access more ethical financing. Thus, Islamic banking can be a strategic partner for MSMEs, assisting them in sustainable business growth and development.